Deconstruction Mechanism in Postmodernism Arts and its Role in Teaching the Artistic Tasting for the Learner: نضال ناصر ديوان (Al-Academy, 2020)
Deconstructionism opened the door wide to multiple readings and restore the reader his authority that he lost in the modernism, thus became more able to decipher the plastic discourse through reconstruction according to what he wants or what the plastic discourse gives him of possibilities beyond consumerism and thus the author has been canceled. The problem of the current research is limited to the following question: does deconstructionism in postmodern arts have a role in teaching the artistic tasting for the learner? The aim of the current research is to reveal the deconstruction work mechanisms in postmodern arts and their role in teaching the artistic tasting for the learner. As for the theoretical framework, the first section focused on the deconstructive criticism and its work mechanisms. The second section dealt with deconstructionism in the postmodern art. The third section addressed the art education and postmodern art. The methodology of the research used the descriptive analytical method and presented the research community and sample which consists of (5) paintings in addition to a description of the performance and the virtual validity procedures. The research ended with the analysis of the sample and the results that resulted in the emergence of the feature of the no form and no subject through evoking automatic media such as spilling and dropping paint and dyes, freeing the energy of color and linear motion and its connection with the physical laws of motion. The most prominent conclusions showed the strangeness of the form and destroying its rules and compensating it with new values which constitutes a protest more than it being an artistic style expressing transient, temporary and timely aesthetic and intellectual concepts in the midst of the modern life dynamism. The research ended up with a set of recommendations and conclusions.